Magnetic-field-free terahertz emission from a magnetic tunneling junction. (2nd September 2019) - Li, Jugeng; Jin, Zuanming; Song, Bangju; Zhang, Shunnong; Guo, Chenyang; Wan, Caihua; Han, Xiufeng; Cheng, Zhenxiang; Zhang, Chao; Lin, Xian; Ma, Guohong; Yao, Jianquan
Abstract: Recently, ferromagnetic (FM) heterostructures have been demonstrated to emit THz radiation induced by femtosecond laser pulses. In such spintronic THz emitters, an in-plane external magnetic field is technological required to assist the orientations of the magnetization, which could be an obstacle for practical micro-electrooptic applications. Here, as a proof-of-concept, THz generation is based on the inverse spin Hall effect of the FM/Ta within a magnetic tunneling junction (MTJ) without external magnetic field. Furthermore, THz emission can be engineered by modulating of the tunneling conductivity within a photoexcited MTJ as the relative magnetizations of two FM layers change their alignments.